Clinical Aspects of Overlap Syndrome - Case Report and Literature Review - Grygiel-Górniak, Bogna; Godtfredsen, Oscar Nicholas; Eid, Gunnar Nyborg; Werczak, Nicholas; Puszczewicz, Mariusz (Archives of Clinical and Biomedical Research, 2018)
We report a patient with overlap syndrome (systemic sclerosis (SSc) and polymyositis (PM)). The heterogeneous nature of systemic sclerosis may lead to a great diversity in the clinical presentation of the disease. With this case report we aim to demonstrate clinical manifestations of systemic sclerosis and polymyositis in an overlap-syndrome, with support from antibody profile and laboratory data.